Sterile cities? The rlationship between allergy and urban trees - Szabó, Krisztina; Balogh, Péter István; Riesz, Adrienn (4D Journal of Landscape Architecture and Garden Art, 2023)
Urban blight affects billions of city dwellers worldwide. Green spaces and trees are the best way to mitigate the adverse effects of climate change or urban climate, and they raise a wide range of health issues. In addition to pollution, there is increasing talk of allergies, a global public health problem. This article aims to analyse the complex relationship between urban green spaces and allergic diseases, from a medical, horticultural, and landscape architecture perspective. It is becoming increasingly difficult to create a liveable environment around us with few (and fewer) urban 'survivors' to choose from. A recent draft proposal would restrict or ban the planting of any tree species with at least two scientific publications in peer-reviewed journals supporting its allergenicity. Restrictions and bans would primarily limit the use of wind-pollinated plants, while evolution is moving towards wind pollination rather than insect pollination. Restrictions, especially bans, are a very powerful tool that can easily end up having the opposite effect to the original intention. Public health is a fundamental issue for everyone, yet before adopting legislation that can be considered definitive, it is worth considering the arguments from the point of view of tree protection, showing what our environment would be like, what ecosystem services we could expect if we were surrounded only by climate-tolerant but non-allergenic taxa. In addition to reviewing the state of allergy and plant allergy in our country, we also have a strong aim to bring the "two societies" closer together. We believe that by finding common ground between the medical, public health, and green professions, we can move urban plant use in a direction that will create a better, more aesthetic, and above all, healthier and more liveable environment for urban dwellers.
Keywords: tree species; allergen; environmental impact; livable environment